The influence of the grafting density of glycopolymers on the lectin binding affinity of block copolymer micelles. (20th December 2017) - Pröhl, Michael; Seupel, Susanne; Sungur, Pelin; Höppener, Stephanie; Gottschaldt, Michael; Brendel, Johannes C.; Schubert, Ulrich S.
Abstract: The integration of natural carbohydrates as ligands for the targeting of specific cell types into synthetic drug delivery systems such as polymer micelles has gained increasing attention, which is based on the expression of selective receptors or lectins in the cell membrane. While several structural aspects of this interaction are well-understood, only limited knowledge exists on the impact of the grafting density of sugar groups on this interaction. In the presented approach, we created core-shell-corona micelles with comparable size and shape, but a variable density ofd -mannosylated chains sticking out from the surface, and investigated their interaction with the lectin concanavalin A (Con A). The polymers were synthesized using the reversible addition fragmentation chain transfer polymerization (RAFT) providing excellent control and narrow distributions for all materials. The blocks based on butyl acrylate and N -acryloyl morpholine form the core and shell of the micelles, respectively, while an additionald -mannosylated block, which forms the corona, is introduced applying a previously reported post-polymerisation functionalization of a reactive bromine precursor with α-d -thiomannose. Varying the ratios of the diblock and triblock polymers in the assembly process, the density of thed -mannosylated chains could easily be adjusted in this mixed micelles approach. All micelles revealed sizes of around 50 nm (estimated by light scattering and cryo -TEM) and similar morphologies, an aspect that is crucial for the direct evaluation of the influence of the grafting density on the binding affinity. The subsequent binding studies with the lectin Con A revealed a clear trend that binding affinity increases with increasing sugar content and a minimum of 10% ofd -mannosylated chains is required for an effective and detectible aggregation. However, it is noteworthy that the full coverage of the micelles with sugar chains is detrimental for the binding to Con A and a significant reduction of the clustering rate was observed, while a ligand density of around 50–60% was favorable for the best interaction. These finding substantiate the importance of the ligand density for the design of targeting delivery systems. Graphical abstract: Highlights: The triblock terpolymer P(BA- b -NAM- b -ManEA) P4 self-assembles in H2 O to core-shell-corona micelles. Mixed micelles of varied ratios of P(BA- b -NAM) andP4 were formed in H2 O with similar shape over all tested concentrations. Turbidity studies with the lectin concanavalin A revealed a minimum ligand density of 10% for detectable interactions. Maximum clustering rate were obtained with 50 to 60% of d‑mannosylated chains on the surface of the particles.